INVESTIGATION OF THE RHEOLOGICAL PROPERTIES OF SBS MODIFIED BINDER PRODUCED BY DIFFERENT METHODS - Kok, Baha Vural; Yilmaz, Mehmet; Kuloglu, Necati; Alatas, Taner (Yildiz Technical Univ, 2011)
In this study 4% stiren-butadien-stiren (SBS) was added to base bitumen by 27 different mixing methods including 3 different mixing rates, 3 different mixing times and 3 different mixing temperatures and the rheological properties of these binders were investigated. In addition, binder experiments were carried out for pure bitumen with applying the same mixing methods. Softening point, viscosity and complex modulus values of binders, which were prepared with the methods explained above, were determined. Temperature, which is a variable in the mixing process, is observed as less influential compared to other two variables that are mixing time and mixing rate. Moreover, it is observed that pure binders are affected more than modified binders from mixing parameters. The difference mentioned above is attributed to the fact that pure binder experiences oxidation and evaporation with the mixing conditions, which are becoming harsher, compared to the modified binders do. With the interpretation of experimental data, it is clarified that mixtures, which have similar complex modulus characteristics, can be obtained with different combinations of mixing time, mixing rate and mixing temperature. It is found that viscosity and softening point values of modified binders have a linear relationship above 80 percent. Furthermore, this relationship is valid for complex modulus with softening point and viscosity values. However, correlations between the parameters are seen as more consistent with the slower mixing rates, lower mixing time and temperatures whilst various complex modulus values can be acquired with higher mixing values corresponding to same viscosity and softening point values.
Keywords: Bitumen; SBS; mixing procedure; rheological properties